Fluorodeoxyglucose metabolism associated with tau‐amyloid interaction predicts memory decline. Issue 4 (6th April 2017) - Hanseeuw, Bernard J.; Betensky, Rebecca A.; Schultz, Aaron P.; Papp, Kathryn V.; Mormino, Elizabeth C.; Sepulcre, Jorge; Bark, John S.; Cosio, Danielle M.; LaPoint, Molly; Chhatwal, Jasmeer P.; Rentz, Dorene M.; Sperling, Reisa A.; et al.
Abstract : Objective: The aim of this article was to evaluate in normal older adults and preclinical Alzheimer's disease (AD) the impact of amyloid and regional tauopathy on cerebral glucose metabolism and subsequent memory decline. Methods: We acquired positron emission tomography using F18 flortaucipir (tau), C11 Pittsburgh compound B (amyloid), and F18 fluorodeoxyglucose (FDG) in 90 clinically normal elderly of the Harvard Aging Brain Study. Results: Posterior cingulate metabolism decreased when both amyloid and neocortical tau were high and predicted subsequent memory decline in a larger sample of normal elderly. In contrast, frontal hypometabolism related to the common age‐related entorhinal tauopathy, but this dysfunction was independent of amyloid, and did not predict significant memory decline. Neocortical tauopathy was positively associated with metabolism in individuals with subthreshold amyloid, suggesting that glucose metabolism increases before decreasing in the course of preclinical AD. Interpretation: Our study identified a synergistic effect of amyloid and tau deposits and demonstrated, for the first time, in normal elderly its link to AD‐like hypometabolism and to AD‐like memory decline. The amyloid effect was observed with tau in neocortex, but not with tau in entorhinal cortex, which is the common site of age‐related tauopathy. Entorhinal tau was associated with frontal hypometabolism, but this dysfunction was not associated with memory loss. Ann Neurol 2017;81:583–596